Effectiveness of the tetrapeptide HAEE: an innovative approach to Alzheimer's treatment in experimentation - Evgenii A. Patrakhanov (Research Results in Pharmacology)
Introduction: Alzheimer’s disease (AD) is the most common neurodegenerative disorder, characterized by a progressive decline in cognitive functions. According to the “Alzheimer’s Disease International”, there were 36 million reported cases of AD worldwide in 2009, with projections suggesting an increase to 66 million by 2030 and 115 million by 2050.